Animal amino acid sensor — A review - Yongding Ke; Xinyu Peng; Chengchuang Song; Xingtang Fang; Yanhong Wang; Chunlei Zhang (Animal Bioscience)
Cell growth and metabolism necessitate the involvement of amino acids, which are sensed and integrated by the mammalian target of rapamycin complex 1 (mTORC1). However, the molecular mechanisms underlying amino acid sensing remain poorly understood. Research indicates that amino acids are detected by specific sensors, with the signals being relayed to mTORC1 indirectly. This paper reviews the structures and biological functions of the amino acid sensors identified thus far. Additionally, it evaluates the potential role these sensors play in the developmental changes of the livestock production.